2011
DOI: 10.1042/cs20110303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short- and long-term portal hypertension on adrenergic, nitrergic and sensory functioning in rat mesenteric artery

Abstract: In the present study, we analysed possible alterations in adrenergic, nitrergic and sensory functioning in mesenteric arteries from rats at 1 and 21 months after partial portal vein ligation, and the mechanisms involved in these alterations, if any. For this purpose, we analysed the vasoconstrictor response to EFS (electrical field stimulation) and the effect of the α-antagonist phentolamine, the NOS (nitric oxide synthase) inhibitor L-NAME (N(G)-nitro-L-arginine methyl ester) and the CGRP (calcitonin gene-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 44 publications
6
17
0
Order By: Relevance
“…As we showed in the Results section, after performing a time-course pilot study, we considered it appropriate to perform experiments with either 0.1 µmol/L ketotifen or 0.1 mmol/L tranilast for 3 hours. EFS produced a frequency-dependent contraction in endothelium-intact mesenteric segments from all the experimental groups as reported in previous reports by our group [22,23,29,30]. We observed that ketotifen and tranilast had opposite effects: while preincubation with ketotifen increased the contraction induced by EFS, tranilast decreased that contraction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As we showed in the Results section, after performing a time-course pilot study, we considered it appropriate to perform experiments with either 0.1 µmol/L ketotifen or 0.1 mmol/L tranilast for 3 hours. EFS produced a frequency-dependent contraction in endothelium-intact mesenteric segments from all the experimental groups as reported in previous reports by our group [22,23,29,30]. We observed that ketotifen and tranilast had opposite effects: while preincubation with ketotifen increased the contraction induced by EFS, tranilast decreased that contraction.…”
Section: Discussionsupporting
confidence: 89%
“…Western blot analysis of nNOS and phosphorylated nNOS (P–NOS) expression was performed as previously described [22,23]. Rabbit polyclonal antibody against nNOS (1:1000 dilution, Abcam), rabbit polyclonal antibody against P-nNOS (1:1000 dilution, Abcam), and monoclonal anti-β-actin-peroxidase antibody (1:50000, Sigma-Aldrich, Spain) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Also, blank sample measures were collected in the same way from segment-free medium in order to subtract background emission. Some assays were performed in the presence of either TTX (0.1 mmol/l), the specific nNOS inhibitor 7-NI (0.1 mmol/l) or the specific iNOS inhibitor 1400 W (1 mmol/l) [9,27,28]. The amount of nitric oxide released was expressed as arbitrary units/mg tissue.…”
Section: Nitric Oxide Measurementsmentioning
confidence: 99%
“…The application of electrical field stimulation (EFS) produces a vasoconstrictor response which is the integrated result of the release of different neurotransmitters, mainly noradrenaline from sympathetic nerve endings, nitric oxide from nitrergic innervation and calcitonin gene-related peptide (CGRP) from sensory nerves [4][5][6][7]. Alterations of the functional role of these components in rat mesenteric artery have been associated with several experimental and pathophysiological circumstances including ageing, portal hypertension, liver cirrhosis and diabetes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although lymphatic vessel adaptations in response to prolonged changes in transmural pressure have not yet been reported, guidance may be found in reports detailing the chronic adaptation of blood vessels and ventricles. To study adaptive responses in blood vessels, investigators have used partial constriction to raise upstream transmural pressures and lower downstream transmural pressures in the same vessel (6,37). Therefore, we used partial vessel constriction to test the hypothesis that lymphatic vessels exposed to higher transmural pressures adapt functionally to become stronger pumps than vessels exposed to lower transmural pressures.…”
mentioning
confidence: 99%